Adverse cardiovascular ageing among older women and cardiometabolic ageing. (8th February 2021) - Ho, J; Kovalik, J; Gao, F; Zhao, X; Shuang, L; Teo, L; Tan, R; Ewe, S; Wee, H; Ching, J; Koh, W; Zhong, L; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): National Medical Research Council (NMRC) Background Despite longer life expectancies, women may experience reduced 'health-span' (period of life spent in good health) due to accumulation of risks over their longer life spans. Metabolic factors present in diet and lifestyle may provide modifiable solutions to tackle burdens of cardiovascular (CV) ageing in women. Objective We aim to study gender differences in CV structure and function among community older adults without clinical CV disease, as well as metabolic perturbations in their study samples. Methods We examined a prospective cohort study of older adults, obtaining their medical history, serum sampling, echocardiography and cardiac magnetic resonance (CMR) imaging on a single day visit. Echo E/A ratio was computed as a ratio of peak velocity flow in early diastole E (m/s) to peak velocity flow in late diastole by atrial contraction A (m/s) mitral inflow velocities. Longitudinal strain (ε) at any time point (t) in the cardiac cycle from end-diastole (time 0) was calculated as: ε(t)=(L(t)-L0)/L0, obtaining left atrial (LA) reservoir strain (εs), conduit strain (εe) and booster strain (εa) by CMR. Metabolomics profiling was performed by standard mass spectrometry techniques. Results Among n = 492 (49.6%, n = 244 women, mean age 73 ± 4 years) participants, women had lower prevalence of hypertension (52% vs 58%, p < 0.0001), smoking (4% vs 35%, p < 0.0001), but higher prevalence of dyslipidemia (52% vs 50%, p = 0.001) compared to men. Women had lower left ventricular mass index (69 vs 71 g/m2, p < 0.0001) compared to men. However, women had more adverse CV function, such as lower E/A ratio (0.78 vs 0.85, p < 0.0001), lower LA booster (εa) (16.5 vs 17.8, p = 0.027) and lower LA reservoir (εs) strain rate (1.5 vs 1.6, p = 0.012), compared to men. Amino acids such as alanine, arginine, aspartate, citrulline, glycine, phenylalanine and valine were similar between gender. However, women had higher levels of tyrosine (76 vs 68 μM, p = 0.015). On multivariate adjustment, apart from age, tyrosine was independently associated with E/A ratio (β=0.002, 95%CI 0.00-0.004, p = 0.044) and εs (β=0.004, 95%CI 0.00-0.009, p = 0.048) among women. Conclusion: Utilizing conventional and sensitive CV imaging, women appeared to have more adverse CV functions with ageing. As a branched chain amino acid linked to future risk of CV disease, tyrosine may be linked to adverse CV function. Factors that contribute to these cardiometabolic profiles, such as menopause, diet or lifestyle warrant further research.